2013 13th International Conference on Quality Software 2013
DOI: 10.1109/qsic.2013.43
|View full text |Cite
|
Sign up to set email alerts
|

On the Correlation between the Effectiveness of Metamorphic Relations and Dissimilarities of Test Case Executions

Abstract: Metamorphic testing (MT) is a property-based automated software testing method. It alleviates the oracle problem by testing programs against metamorphic relations (MRs), which are necessary properties among multiple executions of the target program. For a given problem, usually more than one MR can be identified. It is therefore of practical importance for testers to know the nature of good MRs, that is, which MRs are likely to have higher chances of revealing failures. To address this issue we investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Their study on two subject programs showed a strong correlation between coverage and fault-detection effectiveness in one of the two. In a similar study, Cao et al [47] assessed the relation between fault-detection effectiveness of metamorphic relations and test case dissimilarity. An extensive experiment with 83 faulty programs and 7 distance metrics between the execution profiles of source and follow-up test cases revealed a strong and statistically significant correlation between the fault-detection capability of metamorphic relations and the distance among test cases, in particular when using branch coverage Manhattan distance [48].…”
Section: Properties Of Good Metamorphic Relationsmentioning
confidence: 99%
“…Their study on two subject programs showed a strong correlation between coverage and fault-detection effectiveness in one of the two. In a similar study, Cao et al [47] assessed the relation between fault-detection effectiveness of metamorphic relations and test case dissimilarity. An extensive experiment with 83 faulty programs and 7 distance metrics between the execution profiles of source and follow-up test cases revealed a strong and statistically significant correlation between the fault-detection capability of metamorphic relations and the distance among test cases, in particular when using branch coverage Manhattan distance [48].…”
Section: Properties Of Good Metamorphic Relationsmentioning
confidence: 99%
“…Suppose that MR 1 's MTG covers the first and second path and thereby executes statements s 1 and s 2 , and that MR 2 's MTG covers the first and third path and so covers all three statements. This demonstrates that an MR's MTG can obtain greater coverage, if the paths that are traversed by each of its test cases are different (Cao et al 2013). Several guidelines have been proposed to design MRs to have such MTGs.…”
Section: Coveragementioning
confidence: 93%
“…Several guidelines have been proposed to design MRs to have such MTGs. For example, white-box analysis techniques (Dong et al 2013), or coverage information generated by regression testing (Cao et al 2013) could assist in the identification of MRs that have MTGs with different test cases. MRs that use a similar strategy to the SUT tend to have MTGs that have similar source and follow up test cases (Mayer and Guderlei 2006), and thus should be avoided.…”
Section: Coveragementioning
confidence: 99%
See 2 more Smart Citations